Murder by milk bottle ebook - Truss, Lynne (A Constable Twitten Mystery., 2020)
The quirky and charming third crime novel from New York Times bestselling author Lynne Truss. In the wake of two extremely high-profile murder cases, and with the summer of 1957 finally winding down, Constable Twitten is eagerly anticipating a quiet spell at work. But his hoped-for rest is interrupted when he and his colleagues find a trio of bodies, all murdered with the same unusual weapon: a milk bottle. The three victims are seemingly unconnected-a hardworking patrolman, a would-be beauty queen, and a catty BBC radio personality-so Constable Twitten, Sergeant Brunswick, and Inspector Steine are baffled. But with Brighton on high alert and the local newspaper churning out stories of a killer on the loose, the police trio is determined to solve the case and catch the killer. Charming, witty, and full of the joyfully zany characters Truss's readers have come to love, Murder by Milk Bottle will delight old fans and new alike.